2021
DOI: 10.3892/etm.2021.9669
|View full text |Cite
|
Sign up to set email alerts
|

Sodium hydrosulfide alleviates dexamethasone‑induced cell senescence and dysfunction through targeting the miR‑22/sirt1 pathway in osteoblastic MC3T3‑E1 cells

Abstract: Glucocorticoid-induced osteoporosis is characterized by osteoblastic cell and microarchitecture dysfunction, as well as a loss of bone mass. Cell senescence contributes to the pathological process of osteoporosis and sodium hydrosulfide (NaHS) regulates the potent protective effects through delaying cell senescence. The aim of the present study was to investigate whether senescence could contribute to dexamethasone (Dex)-induced osteoblast impairment and to examine the effect of NaHS on Dex-induced cell senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…MC3T3-E1 cells were cultured in α-Minimal Essential Medium (HyClone; Cytiva) supplemented with 10% fetal bovine serum (HyClone; Cytiva), 100 U/ml streptomycin sulfate and 100 mg/ml penicillin. Cells were grown in a humidified incubator with 5% CO 2 at 37˚C ( 18 ). H 2 O 2 was added to the medium to induce an oxidative damage model at a concentration gradient of 0.1, 0.2 and 0.3 mM.…”
Section: Methodsmentioning
confidence: 99%
“…MC3T3-E1 cells were cultured in α-Minimal Essential Medium (HyClone; Cytiva) supplemented with 10% fetal bovine serum (HyClone; Cytiva), 100 U/ml streptomycin sulfate and 100 mg/ml penicillin. Cells were grown in a humidified incubator with 5% CO 2 at 37˚C ( 18 ). H 2 O 2 was added to the medium to induce an oxidative damage model at a concentration gradient of 0.1, 0.2 and 0.3 mM.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 SIRT1 downregulation is also reported to be involved in the regulation of dexamethasone-induced osteoblastic dysfunction, chondrocyte matrix degeneration and osteoporosis. [16][17][18] Nevertheless, the regulatory mechanism of SIRT1 in Dex-induced growth retardation remains unclear.…”
Section: Instructionmentioning
confidence: 99%
“…Importantly, previous studies have suggested that SIRT1 promoted growth plate chondrogenesis and longitudinal bone growth 14,15 . SIRT1 downregulation is also reported to be involved in the regulation of dexamethasone‐induced osteoblastic dysfunction, chondrocyte matrix degeneration and osteoporosis 16–18 . Nevertheless, the regulatory mechanism of SIRT1 in Dex‐induced growth retardation remains unclear.…”
Section: Instructionmentioning
confidence: 99%
“…An increasing number of studies have suggested that osteoblast dysfunction disrupts the balance between bone resorption and bone formation by inhibiting osteoblast differentiation and proliferation, and enhancing osteoblast apoptosis in glucocorticoid-induced osteoporosis ( 26 , 27 ). Exposure to dexamethasone (DEX) induced the apoptosis of osteoblasts and inhibited MC3T3-E1 cell proliferation ( 28 ).…”
Section: Introductionmentioning
confidence: 99%